2014
DOI: 10.3109/08830185.2014.889129
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Liver in Sepsis

Abstract: Despite the progress made in the clinical management of sepsis, sepsis morbidity and mortality rates remain high. The inflammatory pathogenesis and organ injury leading to death from sepsis are not fully understood for vital organs, especially the liver. Only recently has the role of the liver in sepsis begun to be revealed. Pre-existing liver dysfunction is a risk factor for the progression of infection to sepsis. Liver dysfunction after sepsis is an independent risk factor for multiple organ dysfunction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
375
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(388 citation statements)
references
References 59 publications
5
375
1
7
Order By: Relevance
“…The hepatic tissue shows hepatocytes necrosis and edema in sepsis. Additionally, ALT and AST, which represent the degree of liver injury, are significantly increased [26,27]. The kidney is one of the most vulnerable organs in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic tissue shows hepatocytes necrosis and edema in sepsis. Additionally, ALT and AST, which represent the degree of liver injury, are significantly increased [26,27]. The kidney is one of the most vulnerable organs in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury in sepsis progresses from active hepatocellular dysfunction to liver damage and finally to liver failure [3]. The liver performs a wide range of biological functions in metabolic and immunological homeostasis, and contributes to bacterial clearance in sepsis [4]. It has been demonstrated that liver failure is significantly associated with poor prognosis in critically ill sepsis patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing evidence that oxidative stress has an important role in the development of sepsis-induced multiorgan failure (28). As the liver is an important organ affected by oxidative stress both in early sepsis or late sepsis and it plays an important role and it is a major organ responsible for the initiation of multiple organ dysfunction (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%